Implementing Islamic Education Teachers’ Competence in Learning Management at a Public Madrasah in Indonesia - Faruk, Majida; Usman, Syahruddin; Achruh, Andi; Yahdi, Muhammad (International Journal of Educational Evaluation and Policy Analysis, 2026)
This article investigates how Islamic Education teachers implement their professional competence in managing learning at a public Islamic senior secondary school in North Maluku, Indonesia. Teacher competence is understood as a multidimensional construct that includes pedagogical, professional, personal, social, and spiritual dimensions and is expressed through lesson planning, classroom instruction, and learning assessment. Using a qualitative naturalistic design, data were collected through participant observation, in depth interviews with teachers, school leaders, and students, and documentation of lesson plans and institutional records. The findings show that lesson planning is carried out consistently and aligned with the curriculum, but the depth and creativity of plans vary between teachers, with some documents remaining largely administrative. In classroom instruction, teachers demonstrate sincere efforts to create a conducive learning climate, connect Islamic teachings with students daily lives, and encourage participation, although limited use of educational technology, differences in student engagement, and classroom management challenges constrain the consistency of instructional quality. Assessment practices employ diverse techniques to evaluate cognitive, affective, and psychomotor domains, yet the systematic use of formative and authentic assessment is still uneven due to workload and time pressures. Supporting factors include institutional backing through workshops and subject teacher forums, supportive leadership, adequate facilities, and teacher experience, while inhibiting factors comprise internal limitations in instructional design, external constraints related to technology and student diversity, and structural administrative demands. Overall, the study offers an integrated and context specific picture of how competence in learning management contributes to students understanding, motivation, and religious character.